Qualitative Analysis of Borax in the Meatballs by Using Turmeric Extract - Nastiti Utami (Jurnal Pengabdian Masyarakat MIPA dan Pendidikan MIPA, 2021)
Education on health risk of borax and the production of turmeric paper for simple qualitative analysis of borax in food has been conducted in Krasak, Trucuk, Klaten.The purpose of the community service was to provide solutions for prevent the consumption of food products containing prohibited food additives.The methods used in this community service were: education on health risk of borax for health types of harmful food additives, characteristics of foods containing borax, and workshop to make turmeric paper. Qualitative analysis conducted based on curcumin contained in turmeric extract can be used to break down borax bonds into boric acid and bind them to complex boron cyanocurcumin. Discoloration from yellow to redness in turmeric paper can be used as a natural indicator ingredient to detect the presence of borax. The result of this activity is an increase in public knowledge known from post test results and satisfactory responses 85.25% of the results of questionnaires that reveal was very interesting.